Recent advances in forensic medicine and toxicology - Biswas, Gautam, 1972- (Jaypee Medical Pub., 2015)
Recent Advances in Forensic Medicine and Toxicologyprovides all the recent updates on medical jurisprudence, clinical forensic medicine and forensic pathology to help forensic specialists, as well as medical professionals who need to seek the opinion of a forensic specialist in medicolegal cases.